2012
DOI: 10.1080/02640414.2012.660188
|View full text |Cite
|
Sign up to set email alerts
|

Sleep duration and quality in elite athletes measured using wristwatch actigraphy

Abstract: Sleep is known to be an important component of recovery from training, yet little is known about the quality and quantity of sleep achieved by elite athletes. The aim of the present study was to quantify sleep in elite athletes using wristwatch actigraphy. Individual nights of sleep from a cohort of Olympic athletes (n = 47) from various sports were analysed and compared to non-athletic controls (n = 20). There were significant differences between athletes and controls in all measures apart from 'time asleep' … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

27
295
10
12

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 321 publications
(344 citation statements)
references
References 21 publications
27
295
10
12
Order By: Relevance
“…Previous research has reported poor sleep in elite athletes, but with limited comparisons to controls [21,34,35]. Here, we found that elite athletes, as compared to controls, experienced poorer sleep, as evidenced by degraded sleep quality, difficulty falling asleep, more sleep disturbances, greater sleep medication use, and daytime dysfunction.…”
Section: Study Findingssupporting
confidence: 45%
See 3 more Smart Citations
“…Previous research has reported poor sleep in elite athletes, but with limited comparisons to controls [21,34,35]. Here, we found that elite athletes, as compared to controls, experienced poorer sleep, as evidenced by degraded sleep quality, difficulty falling asleep, more sleep disturbances, greater sleep medication use, and daytime dysfunction.…”
Section: Study Findingssupporting
confidence: 45%
“…Of the 37 studies included in the review, only three (8%) incorporated a control-group study design. In a comparison between 46 British Olympic athletes and 20 non-athletes based on actigraphic recordings of sleep, Leeder and co-authors documented that the athletes exhibited lower sleep efficiency due to longer sleep latencies and more wake after sleep onset [21]. Based on assessments using the Pittsburgh Sleep Quality Index (PSQI), Tsunoda and colleagues reported that Japanese wheelchair basketball athletes had poorer sleep quality and sleep efficiency than able-bodied non-athletes [35].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, disordered sleep can negatively affect athletic performance, namely the task execution and mood states (Lastella et al, 2014a). Although it has been reported that sleep quality and quantity are usually poor prior to competition (Halson, 2014), and coping strategies are certainly required, as demonstrated in boaters, before and during a long distance race (Léger et al, 2008), few studies have evaluated sleep in athletes before a competition (Erlacher et al, 2011;Lastella et al, 2014a;Leeder, Glaister, Pizzoferro, Dawson, & Pedlar, 2012;Léger et al, 2008;Silva et al, 2012).…”
Section: Introductionmentioning
confidence: 99%